Optimalisasi Pendapatan Asli Daerah (PAD) Upaya Peningkatan Kinerja Penyelenggaraan Pemerintah Kabupaten Lampung Utara - Desyadi Desyadi; Murtir Jeddawi; Muh. Ilham; Faria Ruhana (Universitas Batanghari Jambi, 2023)
This study aims to analyze the optimization of increasing PAD North Lampung Regency Government which is one of the regencies in Lampung Province which has a lot of potential resources to be developed and managed optimally. Optimizing regional own-source revenue (PAD) is an effort to improve the performance of local government administration as stated in the vision and mission and then implemented through planning document programs and activities (RPJPD, RPJMD and RKPD). This research is a qualitative research with data collection methods using qualitative descriptive research methods. Data sources were obtained through interviews, observations and documents. After the collected data was analyzed again, data analysis techniques were used, namely the SWOT analysis method was used for data reduction, data presentation and data verification. This study was conducted in several SKPD that have the potential to produce PAD which has not been maximized so far. The results of the study show that the strategic environment related to PAD management in North Lampung Regency is produced with ordinate values of x= -0.03 and y = 0.55 which indicates that the SWOT results of this study are in quadrant III, namely a position that is weak internally but still has a chance to be developed. The suggested strategy to be a top priority for efforts to optimize PAD management in North Lampung Regency is the Weaknes-Opportunities Strategy.